Comparison of matrix metalloproteinase-9 and E-cadherin expression in early- and late-onset preeclampsia - Samara, Tjam Diana; Wibowo, Heri; Liem, Isabella Kurnia; Prijanti, Ani Retno; Andrijono, Andrijono (Faculty of Medicine, Universitas Trisakti, 2021)
BACKGROUNDPreeclampsia (PE) is one of the most common pregnancy complications worldwide. Turnover of villous trophoblast is affected by impaired placental perfusion in preeclampsia. Among the various factors that influence pro and antiangiogenic factors in trophoblast invasion of PE are E-cadherin and matrix metalloproteinase-9 (MMP-9). The current classification scheme differentiates PE into two variants early-onset (EO) and late-onset (LO) PE. The aim of this study was to compare MMP-9 and E-cadherin expression between early- (EO) and late-onset (LO) PE. METHODSThis study used a cross-sectional design involving 26 women with gestational age <34 weeks (EO) and 38 women with gestational age ≥34 weeks (LO) from PE patients. Placentas born to preeclamptic mothers were taken in the form of small pieces of the maternal side to measure the levels of MMP-9 and E-cadherin by the ELISA method. Statistical analysis was assessed using the Mann Whitney and independent t-test with a significant p value <0.05. RESULTSSemiquantitative proteinuria levels were significantly higher in EO-PE group compared to LO-PE group (p=0.000). Mean E-cadherin levels were significant lower in the EO-PE group (125.94 ± 54.22 pg/mg) compared to LO-PE group (157.95 ± 54.12 pg/mg) (p=0.024). However, there was no significance difference in median MMP-9 levels between EO-PE group and LO-PE group (p=0.376). CONCLUSIONThis study demonstrate that E-cadherin had lower levels in preeclampsia patients who gave birth <34 weeks. This study indicated that lower levels of e-cadherin can lead to early delivery in preeclampsia patients.